2a+6-10a=

Simple and best practice solution for 2a+6-10a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+6-10a= equation:


Simplifying
2a + 6 + -10a = 0

Reorder the terms:
6 + 2a + -10a = 0

Combine like terms: 2a + -10a = -8a
6 + -8a = 0

Solving
6 + -8a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -8a = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -8a = 0 + -6
-8a = 0 + -6

Combine like terms: 0 + -6 = -6
-8a = -6

Divide each side by '-8'.
a = 0.75

Simplifying
a = 0.75

See similar equations:

| =25n-10+3-8 | | 7.5=3+x/2 | | 24a+72b+40c= | | 5(w+10)+2x+3(2x)=700 | | 7x+4=4(x-11) | | (4*r)*13= | | 7y-12y+3y= | | 4(8+m)=2m+16 | | 4+7=(3-9v) | | lnx^5/2-0.5lnx=ln25 | | 15c+7=11c+35 | | -5(-4+9x)= | | 7r=2(4r-9) | | (9y/14)/(6/14) | | -7(x+1)+7(7+x)= | | 2x+(2x-8)=72 | | X-7/8=-7/12 | | X(-2x+5)=33 | | 6m-3=1/3m | | -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] |

Equations solver categories